Bispecific antibodies: design, therapy, perspectives - Sedykh SE; Prinz VV; Buneva VN; Nevinsky GA (Dove Medical Press, 2018)
Sergey E Sedykh, Victor V Prinz, Valentina N Buneva, Georgy A Nevinsky Laboratory of Repair Enzymes, Siberian Branch of Russian Academy of Sciences Institute of Chemical Biology and Fundamental Medicine, Novosibirsk State University, Novosibirsk, Russia Abstract: Antibodies (Abs) containing two different antigen-binding sites in one molecule are called bispecific. Bispecific Abs (BsAbs) were first described in the 1960s, the first monoclonal BsAbs were generated in the 1980s by hybridoma technology, and the first article describing the therapeutic use of BsAbs was published in 1992, but the number of papers devoted to BsAbs has increased significantly in the last 10 years. Particular interest in BsAbs is due to their therapeutic use. In the last decade, two BsAbs – catumaxomab in 2009 and blinatumomab in 2014, were approved for therapeutic use. Papers published in recent years have been devoted to various methods of BsAb generation by genetic engineering and chemical conjugation, and describe preclinical and clinical trials of these drugs in a variety of diseases. This review considers diverse BsAb-production methods, describes features of therapeutic BsAbs approved for medical use, and summarizes the prospects of practical application of promising new BsAbs. Keywords: bispecific antibodies, therapeutic antibodies, monoclonal antibodies